On the Dependence of Rheology of Hyaluronic Acid Solutions and Frictional Behavior of Articular Cartilage - Rebenda, David; Vrbka, Martin; Čípek, Pavel; Toropitsyn, Evgeniy; Nečas, David; Pravda, Martin; Hartl, Martin (MDPI, 2020)
Hyaluronic acid (HA) injections represent one of the most common methods for the treatment of osteoarthritis. However, the clinical results of this method are unambiguous mainly because the mechanism of action has not been clearly clarified yet. Viscosupplementation consists, inter alia, of the improvement of synovial fluid rheological properties by injected solution. The present paper deals with the effect of HA molecular weight on the rheological properties of its solutions and also on friction in the articular cartilage model. Viscosity and viscoelastic properties of HA solutions were analyzed with a rotational rheometer in a cone–plate and plate–plate configuration. In total, four HA solutions with molecular weights between 77 kDa and 2010 kDa were tested. The frictional measurements were realized on a commercial tribometer Bruker UMT TriboLab, while the coefficient of friction (CoF) dependency on time was measured. The contact couple consisted of the articular cartilage pin and the plate made from optical glass. The contact was fully flooded with tested HA solutions. Results showed a strong dependency between HA molecular weight and its rheological properties. However, no clear dependence between HA molecular weight and CoF was revealed from the frictional measurements. This study presents new insight into the dependence between rheological and frictional behavior of the articular cartilage, while such an extensive investigation has not been presented before.v

Hyaluronic acid (HA) injections represent one of the most common methods for the treatment of osteoarthritis. However, the clinical results of this method are unambiguous mainly because the mechanism of action has not been clearly clarified yet. Viscosupplementation consists, inter alia, of the improvement of synovial fluid rheological properties by injected solution. The present paper deals with the effect of HA molecular weight on the rheological properties of its solutions and also on friction in the articular cartilage model. Viscosity and viscoelastic properties of HA solutions were analyzed with a rotational rheometer in a cone–plate and plate–plate configuration. In total, four HA solutions with molecular weights between 77 kDa and 2010 kDa were tested. The frictional measurements were realized on a commercial tribometer Bruker UMT TriboLab, while the coefficient of friction (CoF) dependency on time was measured. The contact couple consisted of the articular cartilage pin and the plate made from optical glass. The contact was fully flooded with tested HA solutions. Results showed a strong dependency between HA molecular weight and its rheological properties. However, no clear dependence between HA molecular weight and CoF was revealed from the frictional measurements. This study presents new insight into the dependence between rheological and frictional behavior of the articular cartilage, while such an extensive investigation has not been presented before.v
On the Dependence of Rheology of Hyaluronic Acid Solutions and Frictional Behavior of Articular Cartilage
Keywords: articular cartilage; hyaluronic acid; rheology; friction; articular cartilage; hyaluronic acid; rheology; friction